Migration experiences of Jordanian nurses working in the UK - Al-Nawafleh, Ahmad H. (2008)
Background. Many nurses have migrated to the United Kingdom (UK) as a result of workforce shortages in the health care system. This is part of worldwide shortages, which creates international mobility for professionals, in health and other sectors, a migration, which has consequences for source and host countries. Literature on migration is limited by the lack of accurate data and rigorous studies, but a range of theoretical frameworks address issues explaining push and pull factors, and consequences of migration for individuals. Few studies currently report on the experience of migrant nurses before, during, and after transition. Aim. This study examines the personal and professional experiences of Jordanian nurses migration to the UK. Design and methods. Using a qualitative biographic approach, data about migrant nurses was collected by survey and semi-structured interviews. The UK Nursing and Midwifery Council database was accessed to identify Jordanian migrant nurses, with the population broadened by snowball sampling. In total 52 nurses responded to demographic survey. A subsample of 13 nurses was interviewed in person and 12 were interviewed by telephone. Findings. Three key themes were identified. First, Jordanian nurses have challenged the ‘status quo’ and taken a decision to move to the UK, in response to the push or pull of work conditions, educational opportunities, career development, wages, travel and adventure. Second, ‘source to host country: disconnecting and connecting’ shows that Jordanian nurses disconnected many relations in Jordan or the Gulf States when they moved and established additional work and social relations in the UK. Third, ‘away from home: professional transformation and routes diversion’ reported on the shifting in Jordanian nurses’ professional and personal life in the UK. Conclusion. This thesis argues that while migration theories focus on economic, using a case study of nursing and incorporating the professional and personal helps identify future migration movement.